Pengaruh Literasi Keuangan dan Persepsi Kemudahan Penggunaan Aplikasi Fintech terhadap Perilaku Pengelolaan Keuangan Pribadi - Nuryanti, Erna; Hadi, Syamsul (Mahesa Research Center, 2025)
This article aims to analyze the effect of financial literacy and perceived ease of using fintech applications on the personal financial management behavior of students. The study focuses on how financial knowledge and the ease of accessing digital technology influence students’ budgeting, saving, and long-term financial planning in Bawen, Semarang Regency. To address this issue, the study refers to theories of financial literacy, personal financial management behavior, and perceived ease of digital technology. Data were collected through closed-ended questionnaires using a Likert scale from 122 students who actively use fintech applications and were analyzed quantitatively using multiple linear regression. The study concludes that financial literacy has a positive effect on students’ financial management behavior, while perceived ease of using fintech also has a significant and more dominant influence. Simultaneously, the combination of these variables explains nearly half of the variation in students’ financial management behavior, highlighting the importance of financial education and accessible digital technology to develop healthy, structured, and responsible financial behavior.